Study of Interactions in Some Binary Systems by Ultrasonic Velocity Measurements - Gnanasekaran , K.; Mala, R. (Asian Journal of Chemistry, 2012)
The ultrasonic velocity measurements were carried out for the binary mixtures of ethanol/methanol with the ketones such as acetone, ethyl methyl ketone, acetophenone, cyclohexanone. To study the intermolecular interactions in the components chosen, the observed excess ultrasonic velocity values are compared with the calculated values. When excess ultrasonic velocity is plotted against mole fraction the curve shows maximum at almost 50% by mole fraction. Ethanol shows stronger interaction with the ketones relative to methanol as indicated from ultrasonic data.